Empirical Examination Of Global Expansion Strategies Of Malaysian Companies And Recommendations For Reform - Abdulrahman M, Alalyani (2009)
The report would be focused on the reforming the method used to select the strategies and this is done through proposing for the use of certain conceptual frameworks and model such as the PEST Analysis, Porters five Force Model and/or SWOT Analysis